Electrolytes and Biochemical Changes in Cerebrospinal Fluid in Drowning: Experimental Rabbit Model. (September 2018) - Paulis, Melad G.; Hasan, Eman I.
Abstract : Abstract: The diagnosis of drowning is still a difficult task in forensic science. Biochemical changes in different body fluids have been examined for the identification of drowning. However, none of them alone gives accurate results in the diagnosis of drowning and differentiation of saltwater and freshwater drowning. This study aimed to examine cerebrospinal fluid changes in drowned rabbits. Six groups of rabbits were used including immersed dead rabbits in freshwater or saltwater (as control groups), alive fully conscious rabbits drowned in freshwater and saltwater, and anesthetized rabbits drowned in freshwater and saltwater. Cerebrospinal fluid electrolytes except for potassium levels were significantly higher in rabbits drowned consciously in saltwater than their level in the control group. In rabbit drowned in freshwater, the examined electrolytes decreased significantly. In addition, urea, creatinine, uric acid, glucose, and tumor necrosis factor were different in cases of freshwater and saltwater drowning from those of control rabbits. Electrolytes and biochemical changes of unconscious rabbits drowned in water showed no significant difference from those of control rabbits. Cerebrospinal fluid examination in drowning gives promising results in the diagnosis of drowning. In addition, the differentiation between freshwater and saltwater drowning was possible.